2020
DOI: 10.1097/sla.0000000000004047
|View full text |Cite
|
Sign up to set email alerts
|

The Largest Single Center Report on Pediatric Liver Transplantation

Abstract: Objective: We described our experiences on pediatric liver transplantation (LT) from the largest LT center in the world termed the Shiraz Transplant Center. Background: After the first successful pediatric LT in 1967, pediatric LT has become the routine treatment for children with liver failure worldwide. Methods: Data on a total of 1141 pediatric cases of LT were collected. Specifics on baseline and anthrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…Infection rates after liver transplantation among the pediatric population are variable between studies. Nikeghbalian et al [5] reported in-hospital infection rates in a large series of pediatric patients to be 9.4%, moreover infections constituted 35.2% of all causes of death in this population. Another experience from Korea reported the 6 month infection rate among pediatric patients to be 44.2% and similar to the previous report infections were the most common cause of death (50%) [6].…”
Section: Discussionmentioning
confidence: 84%
“…Infection rates after liver transplantation among the pediatric population are variable between studies. Nikeghbalian et al [5] reported in-hospital infection rates in a large series of pediatric patients to be 9.4%, moreover infections constituted 35.2% of all causes of death in this population. Another experience from Korea reported the 6 month infection rate among pediatric patients to be 44.2% and similar to the previous report infections were the most common cause of death (50%) [6].…”
Section: Discussionmentioning
confidence: 84%
“…The probability of acute rejection (ACR) remains 20-40% without the application of an effective immunosuppressive regimen following LT [7]. Long-term immunosuppressant use is required, which has associated complications (e.g., renal injury, abnormal metabolic syndrome, de novo tumors), and the long-term outcomes remain unsatisfactory [8][9][10][11]. There is a need to explore effective immunomodulatory means to induce immune tolerance in LT, mitigate ACR, and decrease or avoid the use of immunosuppressive agents.…”
mentioning
confidence: 99%
“…The most common etiologies for LT were alcoholic liver disease (ALD), nonalcoholic steatohepatitis (NASH), and hepatitis C virus (HCV) (4)(5)(6). For pediatric patients, the leading cause of LT was biliary atresia (7). Posttransplantation infections often occur after LT, with an incidence ranging from 5% to 48% due to the application of immunosuppressants and glucocorticoids (8,9).…”
Section: Introductionmentioning
confidence: 99%